PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA PT. TASPEN (PERSERO) KCU MAKASSAR - Miftah Farid Salam; Mariam Makmur; Kurniawan Kurniawan (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
This research aims to find out whether job satisfaction influences the organizational commitment of employees at PT. Taspen (Persero) KCU Makassar. This data collection uses a quantitative approach and primary data sources in the form of questionnaires which are distributed to the entire research population using probability sampling. The population is all employees of PT. Taspen (Persero) KCU Makassar, while the sample is 149 people, has also been tested for regression and correlation, analysis methods and hypothesis testing. The data analysis method uses multiple regression techniques. The research results show that there is no positive and significant influence of compensation on organizational commitment, there is a positive and significant influence of job characteristics on organizational commitment. There is a positive and significant influence on organizational commitment, and there is a positive and significant influence on organizational commitment. This shows that job satisfaction has a positive and significant effect on organizational commitment at PT. Taspen (Persero) KCU Makassar.